Kajian Ruang Terbuka Publik di Kota Kotamobagu - Maulana Suheryanto; Esli Takumansang; Cynthia Wuisang (Universitas Sam Ratulangi, 2021)
Public open space is a necessity in an urban area because it is equipped with supporting facilities for active and passive community activities, either alone or in groups. Kotamobagu City has 35 public open spaces, but the available supporting facilities are not evenly distributed, resulting in some public open spaces being rarely visited because they cannot serve the needs of the community. This study aims to analyze the need for public open space and the need for public open space facilities in Kotamobagu City. The research method used in this research is descriptive qualitative using standard parameters of the Minister of Public Works Regulation No. 5 of 2008 concerning Guidelines for the Provision and Utilization of Green Open Space in Urban Areas and the radius of reaching social facilities according to Hugh Barton.The results of this study indicate that the need for public open space based on the population is adequate. The need for public open space based on the radius of achievement in Kotamobagu Utara and West Kotamobagu Districts has covered all settlements, but Kotamobagu Timur and South Kotamobagu Districts do not cover all settlements, requiring additional public open space. The need for public open space facilities requires the addition of all available public open space units in Kotamobagu City. Keyword: Public Open Space; Public Open Space Facilities; Kotamobagu City